Rural Financial Management: Moderating Role of Internal Control in the Digital Governance Era.: Meningkatkan Manajemen Keuangan Pedesaan: Peran Moderasi Sistem Pengendalian Internal di Era Tata Kelola Digital. - Isnaini Rochmaniah; Imelda Dian Rahmawati (Academia Open, 2024)
This research investigates the impact of Information Technology Advancement (IT) in rural areas, particularly the Village Financial Management System (Siskeudes), with a focus on its interaction with internal control systems. Through a sample of 30 village secretaries and treasurers in the Buduran District, Sidoarjo Regency, the study employs direct surveys and questionnaires for data collection. Utilizing IBM SPSS Statistics 25, the analysis reveals a significant positive influence of both internal control systems and IT advancement on rural financial management. Notably, internal control systems were found to moderate the relationship between IT advancement and financial governance. These findings underscore the vital role of internal controls in optimizing the benefits of IT solutions, offering valuable insights for global policymakers and practitioners involved in rural development and digital governance.Highlights : The research examines the synergy between Information Technology Advancement and Internal Control Systems in rural financial management. Findings reveal a significant positive influence of both Internal Control Systems and IT advancement on rural financial governance. Internal Control Systems play a crucial moderating role in enhancing the impact of IT solutions, providing essential insights for global policymakers and practitioners in rural development and digital governance. Keywords:Information Technology Advancement, Village Financial Management System, Internal Control Systems, Rural Development, Digital Governance.